Racial Disparities in Surgical Outcomes After Spine Surgery: An ACS-NSQIP Analysis. Issue 6 (September 2019) - Sanford, Zachary; Taylor, Haley; Fiorentino, Alyson; Broda, Andrew; Zaidi, Amina; Turcotte, Justin; Patton, Chad
Study Design: Retrospective cohort study. Objectives: Racial disparities in postoperative outcomes are unfortunately common. We present data assessing race as an independent risk factor for postoperative complications after spine surgery for Native American (NA) and African American (AA) patients compared with Caucasians (CA). Methods: The American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database was queried for spine procedures performed in 2015. Data was subdivided by surgery, demography, comorbidity, and 30-day postoperative outcomes, which were then compared by race. Regression was performed holding race as an independent risk factor. Results: A total of 4803 patients (4106 CA, 522 AA, 175 NA) were included in this analysis. AA patients experienced longer length of stay (LOS) and operative times ( P < .001) excluding lumbar fusion, which was significantly shorter ( P = .035). AA patients demonstrated higher comorbidity burden, specifically for diabetes and hypertension ( P < .005), while NA individuals were higher tobacco consumers ( P < .001). AA race was an independent risk factor associated with longer LOS across all cervical surgeries (β = 1.54, P <.001), lumbar fusion (β = 0.77, P = .009), and decompression laminectomy (β = 1.23, P < .001), longer operative time in cervical fusion (β = 12.21, P = .032), lumbar fusion (β = -24.00, P = .016), and decompression laminectomy (OR = 20.95, P < .001), greater risk for deep vein thrombosis in lumbar fusion (OR = 3.72, P = .017), and increased superficial surgical site infections (OR = 5.22, P = .001) and pulmonary embolism (OR = 5.76, P = .048) in decompression laminectomy. NA race was an independent risk factor for superficial surgical site infections following cervical fusion (OR = 14.58, P = .044) and decompression laminectomy (OR = 4.80, P = .021). Conclusion: AA and NA spine surgery patients exhibit disproportionate comorbidity burden and greater 30-day complications compared with CA patients. AA and NA race were found to independently affect rates of complications, LOS, and operation time.